Extracranial–Intracranial Cerebral Revascularization: Indications and Results - Raso, Jair Leopoldo; Scaldaferri, Paulo Mallard; Barbosa, Rafael de Albuquerque (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2015)
Objective To present a case-series study of extracranial–intracranial (EC–IC) bypass procedures performed in our service and evaluate indications and results.Method The medical records of 30 patients undergoing 32 EC–IC anastomosis procedures were evaluated. Seventeen patients were male (56.6%). The age ranged from 26 to 85 years (mean: 58.2). The follow-up ranged from 1 to 211 months (mean: 54). We evaluated the indications and complications of the surgical procedures.Results The bypass procedures comprised 28 STA–MCA anastomosis (87,5%) and four posterior circulation anastomosis. The main indications included cervical internal carotid artery occlusion (19 cases), Moyamoya disease (3 cases), giant aneurysms (3 cases), intracranial arterial stenosis (2 cases), and vertebral–basilar insufficiency (3 cases). On follow-up, graft patency was 93.7%, confirmed in half of the cases by arterial digital subtraction angiography, magnetic resonance angiography, and CT angiography. There was no surgical mortality. Three patients had PO complications (9.3%), including one case of ischemia (3.1%).Conclusion The EC–IC bypass is a procedure with low morbidity and mortality. The indication of EC–IC bypass surgery for cerebral atherosclerotic disease should not be generalized. The EC–IC bypass can be indicated for cerebral revascularization in Moyamoya disease, intracranial stenosis, and in the management of complex aneurysms. This procedure can be an alternative in the treatment of vertebral–basilar insufficiency.
Keywords: cerebral revascularization; extracranial–intracranial bypass; superficial temporal artery; middle cerebral artery